2016
DOI: 10.3109/10903127.2015.1115932
|View full text |Cite
|
Sign up to set email alerts
|

Locating AED Enabled Medical Drones to Enhance Cardiac Arrest Response Times

Abstract: Although there are still many factors to consider, drone networks show potential to greatly reduce life-saving equipment travel times for victims of cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(101 citation statements)
references
References 17 publications
1
96
3
1
Order By: Relevance
“…Research into AED drones are timely because of recent attention towards the prehospital period (i.e., symptom onset to emergency department arrival) to reduce total ischemia burden time (i.e., symptom onset to reperfusion) [22]. In 2016, Pulver et al developed a geographical approach for distribution of an AED-equipped drone network, designed to minimize travel time to reach OHCA victims [23•]. Investigators used census block groups for demographic data and cardiac incidence rates to develop three potential drone network configurations to cover a geographically diverse region of 2080 km2.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research into AED drones are timely because of recent attention towards the prehospital period (i.e., symptom onset to emergency department arrival) to reduce total ischemia burden time (i.e., symptom onset to reperfusion) [22]. In 2016, Pulver et al developed a geographical approach for distribution of an AED-equipped drone network, designed to minimize travel time to reach OHCA victims [23•]. Investigators used census block groups for demographic data and cardiac incidence rates to develop three potential drone network configurations to cover a geographically diverse region of 2080 km2.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators used census block groups for demographic data and cardiac incidence rates to develop three potential drone network configurations to cover a geographically diverse region of 2080 km2. Investigators used GIS to compare travel times between current EMS data (from existing EMS infrastructure) and determined optimal spatial configurations of a medical drone network [23•]. Investigators found that a network of drones could cover 90% of cardiac arrest demand within a minute, as compared to the current response coverage of 4.3% with current EMS organization [23•].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drones can be remotely dispatched by the EMD and with full automation fly to the site of the OHCA. Currently, there are many obstacles such as legislation and practical implementation issues, but simulation studies and theoretical models have shown promising results in reducing response time in OHCA [34,77].…”
Section: Aed Retrieval By Bystander or Mobile Respondersmentioning
confidence: 99%
“…3. Hardy et al (2017) Mapping malaria vector habitats Pulver et al (2016) Transporting automated external defibrillators Chabot and Francis (2016) Bird detection Hodgson et al (2017) Surveying marine fauna Sankey et al (2017) Forest monitoring Casella et al (2017) Mapping coral reefs Szantol et al (2017) Mapping orangutan habitat Chowdhury et al (2017) Disaster response and relief Restas (2015) Supporting disaster management (earthquakes, floods, fires) Source Own elaboration from different sources …”
Section: Us$) Sourcementioning
confidence: 99%